Excretion of Avenanthramides, Phenolic Acids and their Major Metabolites Following Intake of Oat Bran. Issue 2 (29th December 2017) - Schär, Manuel Y.; Corona, Giulia; Soycan, Gulten; Dine, Clemence; Kristek, Angelika; Alsharif, Sarah N. S.; Behrends, Volker; Lovegrove, Alison; Shewry, Peter R.; Spencer, Jeremy P. E.
Abstract : Scope: Wholegrain has been associated with reduced chronic disease mortality, with oat intake particularly notable for lowering blood cholesterol and glycemia. To better understand the complex nutrient profile of oats, we studied urinary excretion of phenolic acids and avenanthramides after ingestion of oat bran in humans. Methods and results: After a 2‐d (poly)phenol‐low diet, seven healthy men provided urine 12 h before and 48 h after consuming 60 g oat bran (7.8 μmol avenanthramides, 139.2 μmol phenolic acids) or a phenolic‐low (traces of phenolics) control in a crossover design. Analysis by ultra‐high performance liquid chromatography (UPLC)–MS/MS showed that oat bran intake resulted in an elevation in urinary excretion of 30 phenolics relative to the control, suggesting that they are oat bran‐derived. Mean excretion levels were elevated between 0–2 and 4–8 h, following oat bran intake, and amounted to a total of 33.7 ± 7.3 μmol total excretion (mean recovery: 22.9 ± 5.0%), relative to control. The predominant metabolites included: vanillic acid, 4‐ and 3‐hydroxyhippuric acids, and sulfate‐conjugates of benzoic and ferulic acids, which accounted collectively for two thirds of total excretion. Conclusion: Oat bran phenolics follow a relatively rapid urinary excretion, with 30 metabolites excreted within 8 h of intake. These levels of excretion suggest that bound phenolics are, in part, rapidly released by the microbiota. Abstract : The urinary excretion of potentially bioactive phenolic acids and avenanthramides in oats is determined in a randomized controlled trial. Following intake of 147 μmol phenolics in 60 g oat bran, urinary excretion of 30 phenolic metabolites is significantly higher relative to the control at 0–2 h and 4–8 h after intake. On average 22.9% of the ingested dose is recovered predominantly as vanillic acid, hydroxyhippuric acid, and sulfate conjugates of benzoic and ferulic acid.